Transformasi Paradigma Manajeman Keilmuan Sekolah Dasar Menuju Pendidikan Dasar Islam - Marli, Zainal Anshari (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
Islami Elementary School is combination Islamic education institution that was born from non formal education in Islamic boarding school formed as formal education of madrasah with elementary school as the continuing of Sekolah Rakyat (SR). This school is an elementary school formed by Dutch colonialist for the local students in Indonesia as the basic need of education. Sekolah Rakyat for the next transformation become elementary school created to make a combination the heritage of colonial education with the heritage of Indonesian Islamic education so that it is called Islamic Elementary School that still drive formal education mission and madrasah generally. Islamic Elementary School is a respond of muslim that shown by doing some innovation and creation of development of education institution in a complex society. Islamic elementary school not always using Islamic term, some of them stil use elementary school but the subject elaborate between elementary school and Madrasah Ibtidaiyah, so the content of this school become an Islamic Elementary School. It means the combination elementlary school with Madrasah Ibtidaiyah like Elementary Full Day School al-Baitul Amien Jember as the object focus of this paper.